Private defence in Malaysia: the dos and don’ts - Roslim, Salmah; Abu Bakar, Syatirah; Abdullah@Abd Halim, Mohd Zulhelmey (Universiti Teknologi MARA, Kedah, 2025)
Private defence is a vital legal right in Malaysia, designed to protect individuals from harm when faced with unlawful threats. Provided in Sections 96 to 106 of the Penal Code, this right allows people to defend themselves, others, or their property when immediate danger arises. However, the law is clear that this right is not absolute. It can only be used when there is a genuine and imminent threat, and the actions taken must be reasonable and proportional to the danger. Notably, private defence cannot be used as a pretext for retaliation or planned aggression or in cases where other options, like involving the authorities, are available. By setting these boundaries, Malaysia's legal framework ensures that private defence is a means of justice, empowering individuals to act in critical moments without crossing ethical and legal limits. This balance protects both personal safety and the integrity of the legal system, preventing the misuse of private defence as an excuse for excessive force or vigilantism.